Tổng hợp một số dẫn xuất của axit madecassic phân lập từ cây rau má (Centella asiatica (L.) urban) của Việt Nam - Lộc, Trần Văn; Như, Võ Quỳnh; Thu Hà, Lê Thị; Thư, Nguyễn Minh; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
From the MeOH extract of the Centella asiatica (L.) Urban. was collected in Hanoi, madecasic acid was isolated with 0.37%.w/w. Starting from the madecassic acid 7 new amide derivatives at the 28-COOH group have been synthesized. Their structures were determined by IR, MS and NMR spectroscopic methods. Keywords: Madecassic acid, amide derivative.